Isolation and identification of epiphytic lactic acid bacteria from guinea grass (Panicum maximum) - Pasebani, Mahdi; Yaakub, Halimatun; Sijam, Kamaruzaman; Alimon, Abdul Razak (Science Publications, 2010)
Problem statement: Bacteria can perform a variety of beneficial functions, for example many lactic acid bacteria are responsible for fermentation of silage in the process of forage conservation. In the making of silage, epiphytic lactic acid bacteria are usually insufficient in numbers to promote efficient lactate fermentation. This study was conducted to identify the predominant indigenous bacteria, with emphasis on lactic acid bacteria, from Guinea grass (Panicum maximum). Approach: Two different condition of growth using nutrient and MRS agar were prepared for isolation of the bacteria. In total, 18 purified isolates were identified by BIOLOG identification system which comprised of 9 bacterial species. Standard plate count in the both conditions was considered. Results: Three bacterial species based on the first condition of growth were identified which were belonging to Flavimonas oryzihabitans, Enerobacter cloacae, Sphingomonas paucimobilis B. Lactic acid bacteria based on the second condition of growth were belonging to Weissella confusa, Weissella paramesenteroides, Leuconostoc mesenteroides ssp. dextranicum, Lactococcus lactis ssp. hordniae. Result of plate count showed that 8.3×103 CFU lactic acid bacteria are available per gram of fresh guinea grass. Conclusion: Three hetero-fermentative and one homo-fermentative lactic acid bacteria were identified which would be suggested to use as bacterial inoculants because of the insufficient amount of epiphytic lactic acid bacteria and the availability of pathogenic bacteria in the grass.